The Palm Landscapes of the Italian Riviera. (2nd January 2018) - Piana, Pietro; Watkins, Charles; Balzaretti, Ross
ABSTRACT: Palm trees are today a characteristic feature of tropical tourist landscapes around the world, from the Caribbean to the Maldives. They are also a distinctive element of Mediterranean landscapes. On the Italian Riviera they are frequently found in the grounds of villas and hotels, at railway stations and in public squares. This paper examines the changing landscapes of the palm trees of the Italian Riviera over the last 300 years. Palms, particularly Phoenix dactylifera, were an important element of the local economy cultivated especially for palm fronds to be sold for religious festivals. The widespread presence of palm trees gave stretches of the Ligurian coast in NW Italy an almost tropical character, especially around Bordighera and Sanremo. These coastal towns became major health resorts in the late nineteenth century and international tourists and residents celebrated this exotic landscape. The palms became important subjects for amateur and professional artists and photographers, proliferated in gardens, as street trees and in horticultural collections. They became signature trees for these wealthy therapeutic landscapes. Rapid building development and the decline of the palm trade, however, means that only fragments of the old palm plantations remain today, and these are in need of careful conservation.